2018
DOI: 10.1515/med-2018-0080
|View full text |Cite
|
Sign up to set email alerts
|

High expression levels of fascin-1 protein in human gliomas and its clinical relevance

Abstract: AbstractIntroductionThe fascin-1 protein is a cytoskeleton-like protein, which can prompt structural changes in cell membranes and affect the integrity of intercellular relations to promote invasion and metastasis of tumor cells. In this study, we researched the expression of fascin-1 in glioma. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, 2D magnets such as Fe 3 GeTe 2 , CrGeTe 3 , and CrI 3 , have recently sparked enormous attention, due to their unique magnetism in the 2D limit and expressed potential for application in spintronic devices. However, most of these magnetic materials in the 2D limit are unstable in air, which makes further investigations into their intrinsic magnetism and practical applications difficult.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…On the other hand, 2D magnets such as Fe 3 GeTe 2 , CrGeTe 3 , and CrI 3 , have recently sparked enormous attention, due to their unique magnetism in the 2D limit and expressed potential for application in spintronic devices. However, most of these magnetic materials in the 2D limit are unstable in air, which makes further investigations into their intrinsic magnetism and practical applications difficult.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…Moreover, CrX 3 (X = I, Br, Cl) is usually synthesized with multilayers stacked together by vdW interactions. 6,9,14,[22][23][24][25][26][27][28]30,31,35,53,73,74 So the stacking-induced modifications of the properties need to be systemically discussed. Taking BL MoSSe as a reference, 11 six different stacking patterns (AA-II, AA-ClI, AA-ClCl, AB-ClI, AB-II and AB-ClCl) of BL Cr 2 Cl 3 I 3 are considered, and the optimized geometries are shown in Fig.…”
Section: Effect Of the Stacking Ordersmentioning
confidence: 99%
“…As a possible modulating parameter, magnetism sets up a new routine of developing 2D devices for electronic and spintronic applications. [21][22][23][24] Magnetic fields 14,25 and electric fields 23,[26][27][28] are found to be able to tune the magnetism and tunneling resistance in few-layer CrI 3 23,25-27,29-33 and Cr 2 Ge 2 Te 6 . 14,34 The high magnetic transition temperatures, 14,24,35 various spin configurations, 23,26,27,30,32,36 different electronic properties, 19,37 and higher magnetic anisotropy energy [38][39][40] of semiconducting magnetic materials are the center of the attention in the development of 2D magnetic devices.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, the study by Zhang et al showed that fascin expression in glioma tissue was higher than that of normal brain tissue and that high fascin expression correlated with World Health Organization (WHO) grading of glioma patients. Moreover a multivariate analysis showed that high expression of fascin protein was an independent predictor of the prognosis of patients with glioma [110]. Intriguingly, Wang et al showed that the TCA with anti-fascin activity, imipramine, significantly retarded the proliferation of primary and immortalized glioma cells by inhibiting YAP protein, a recognized oncogene in glioma [56].…”
Section: Cancer Of Central Nervous Systemmentioning
confidence: 99%